The Use of Digital Technology among Basic Certificate Lecturers in Community Colleges - Suhaina Mohamed Zaki; Sharifah Masitah Syed Salim; Jamaliah binti Salbi (INCLUSIVE EDUCATION, 2022)
In the digital era of the latest revolution, the field of education has undergone a transformation towards andragogy and pedagogy digitally. In Malaysia, the spread of the COVID-19 epidemic brought about a new norm change in the national education system. At the level of the Department of Polytechnic Education & amp; Community Colleges (JPPKK), Digital Learning Coordinating Committee of the Department of Polytechnic Education and Community Colleges was established with the role of identifying strategies to address challenges and issues related to digital learning and further strengthen ICT infrastructure and digital learning in Polytechnics and Community Colleges. This includes online teaching and learning (PdPDT) for students with special needs. Several major challenges have been made the basis of this study, namely the knowledge of lecturers on computer technology, the acceptance of lecturers on PdPDT for students with special needs and the use of teaching aids in PdPDT. Therefore, this study was conducted to identify the level of use of digital technology among Basic Certificate lecturers in Community Colleges. The study involved 24 lecturers in 12 Community Colleges offering 8 Basic Certificate programs. This Basic Certificate involves students with special needs Learning Disabilities. This study uses a quantitative method by using a questionnaire approach in collecting data to achieve the objectives of the study by using Statistical Packages For Social Sciences for windows version 20.0 (SPSS). The findings of the study show that all Basic Certificate lecturers have a level of knowledge of computer technology. While the level of acceptance of Basic Certificate lecturers on the level of computer use in the teaching and learning process is also in a high level with a mean score of 4.10 and the level of computer use among Basic Certificate lecturers in the PdP process is also very high with a mean score of 4.43. Overall, the findings show that the use of digital technology among Basic Certificate lecturers in Community Colleges is very good.